ANALISA PERDAGANGAN ANTAR DAERAH KOMODITAS TELUR AYAM RAS DI PROVINSI SUMATERA BARAT - Salfadri, Salfadri (Jurnal Benefita, 2017)
The purpose of this study is to investigate the flow of trade and factors affecting the inter-regional trade of race chicken eggs commodity in West Sumatra. The data used in this analysis are primary and secondary data. Primary data was obtained from survey results to wholesalers of race chicken eggs in 15 districts/cities in West Sumatera Province. The number of samples is 146 wholesalers of race chicken eggs. The secondary data obtained from the Central Bureau of Statistics of West Sumatra. The trade flow of  race chicken egg commodity  between regions in West Sumatera Province is done by descriptive analysis to primary data. Factors affecting inter-regional trade of race chicken eggs were analyzed by multiple regressions based on the developed gravity model. The results showed that inter-regional  trade of race chicken eggs occur between regions that do not produce these commodities with regions that produce these commodities. Besides that there are regions that do not produce these commodities but become the intermediary between the regions that produce race chicken eggs with the regions that do not produce commodities of race cihicken eggs. The results of this study also found that using the primary data of factors affecting inter-regional trade of egg commodity commodities in West Sumatra Province is the difference in price. While using secondary data, it is found that factors affecting inter-regional trade of race chicken eggs are: the number of residents of destination regions, the number of residents of origin regions and distance between the origin regions with the destination regions.Tujuan penelitian ini adalah untuk menyelidiki aliran perdagangan dan faktor-faktor yang mempengaruhi perdagangan antar daerah komoditas telur ayam ras di Sumatera Barat. Data yang digunakan dalam analisa ini adalah data primer dan data sekunder. Data primer diperoleh dari hasil survey ke pedagang besar ayam ras di 15 Kabupaten/Kota di Provinsi Sumatera Barat. Jumlah sampel adalah 146 pedagang besar ayam ras.Data sekunder diperoleh dari Badan Pusat Statistik Sumatera Barat. Aliran perdagangan komoditas telur ayam antar daerah di Provinsi Sumatera Barat dilakukan dengan analisa deskriptif terhadap data primer. Faktor-faktor yang mempengaruhi perdagangan antar daerah komoditi telur ayam ras tersebut dianalisa dengan regressi berganda yang berdasarkan kepada model gravitasi yang dikembangkan. Hasil penelitian menunjukan bahwa perdagangan antar daerah komoditas telur ayam ras terjadi antara daerah yang tidak memproduksi komoditas tersebut dengan daerah yang memproduksi komoditas tersebut. Disamping itu ada daerah yang tidak menghasilkan komoditas tersebut tetapi jadi perantara antara daerah yang memproduksi telur ayam ras dengan daerah yang tidak menghasilkan komoditas telur ayam ras. Hasil penelitian ini juga menemukan bahwa dengan menggunakan data primer faktor-faktor yang mempengaruhi perdagangan antar daerah komoditas telur ayam ras di Provinsi Sumatera Barat adalah selisih harga. Sedangkan dengan menggunakan data sekunder ditemukan bahwa faktor-faktor yang mempengaruhi perdagangan antar wilayah komoditi telur ayam ras adalah: jumlah penduduk daerah tujuan, jumlah penduduk daerah asal dan jarak antar daerah asal dengan daerah tujuan.